The wisdom of Voltaire - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The ideas of Voltaire (François-Marie Arouet) about person and his life are considered. It is revealed that in the centre of philosopher’s reflections is the thesis that person is an active being. It is established that the person’s actions are based on needs and passions, in particular person’s love for himself, which is the basis of both personal existence of human and his interaction with other people. It is noted that the meaning of life for Voltaire consists in truth, freedom, and virtue. The philosopher’s idea of the diverse nature of person freedom, which first of all means the ability to express one’s will and act, is revealed. It is determined that the most important principles of virtuous behaviour are reflected in the following aphorisms: «Do not do what you would not like to be done to you»; «When in doubt, refrain from acting, fair or unfair». It is shown that the main role in uniting people the thinker gives to social justice.
Keywords: person; passions; needs; intelligence; liberty; justice; moral